Innovative Marketing Strategies in Human Resource Management: Improving Organizational and Marketing Performance in the Digital Era - Raharja, Rizki Maulana; Irawan, Moh. Ali Yahya; Fitri, Ainul; Aisyah, Aisyah; Uli, Aprilla Sinta; Mahfuz, Muhammad (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
In the era of digital marketing that continues to grow, the role of social media as an effective marketing platform is increasingly important, especially for the Micro, Small and Medium Enterprises (MSMEs) sector. To achieve success in doing business on social media, the development of human resources (HR) in accordance with the needs of the digital era is crucial. This research reviews the importance of human resource development in the context of digital marketing, especially in advancing the MSME sector on social media. The focus of this research is to consider the knowledge and skills needed by MSME employees in utilizing social media as an effective marketing tool. By implementing the right HR development strategy, MSMEs can get significant benefits, such as increased creativity, adaptation to changing trends, and the ability to compete in the digital marketing era . In the context of human resource development in the era of digital marketing to advance the MSME sector, special training , and access to the latest information and resources are important strategies that need to be implemented